A New Alternative to Cyanidation: Biocatalyzed Bisulfide Leaching - Robert M. Hunter; Frank M. Stewart; Tamara Darsow; Macgregor L. Fogelsong; David W. Mogk; Edwin H. Abbott; Courtney A. Young (Canadian Institute of Mining, Metallurgy and Petroleum, 1998)
Abstract: Development of cost-effective techniques for recovering precious metals from their ores has been the goal of metallurgists for hundreds of years. Today, metallurgists are increasingly called upon to design processes for ores that are refractory to conventional recovery techniques. These challenges and the addition of environmental costs (including site remediation) to the total cost of mining have stimulated a search for alternatives to conventional processes, such as cyanidation. This paper describes the progress made to date in development of an innovative alternative to cyanidation, termed bisulfide leaching, for extracting gold, silver and platinum-group elements from refractory ores and concentrates. While bisulfide leaching can be implemented abiotically, significant benefits accrue from its practice as a bioprocess that integrates the steps of precious-metals liberation and extraction. In many applications, bisulfide leaching appears to offer significant advantages over the traditional cyanidation process. Dissolved bisulfide and hydrogen sulfide are much less toxic than dissolved cyanide and hydrogen cyanide. Recommended workspace exposure limits and harmful concentrations for hydrogen sulfide gas are higher than those for hydrogen cyanide gas. While the facilities required to practice the bioprocess on an industrial scale would be similar to that of cyanidation plants, chemical reagent costs could be 80 percent less. The bioprocess may also offer advantages in the leaching of ores and concentrates that are not amenable to cyanidation. For example, bisulfide leaching of ores containing carbonaceous material may produce higher gold recoveries if the "preg-robbing" characteristic of the material can be controlled biologically or with dissolved sulfide binding. Moreover, in that precious metals are much more soluble than base metals in bisulfide solutions, bisulfide leaching offers distinct advantages over cyanidation for selective dissolution of precious metals from base-metal concentrates. Thus, the bioprocess uses the natural sulfur cycle to mitigate pollutant production and to enhance precious-metals recovery.